2013
DOI: 10.1177/1535370213489488
|View full text |Cite
|
Sign up to set email alerts
|

Soy extracts suppressed iodine uptake and stimulated the production of autoimmunogen in rat thyrocytes

Abstract: Soy consumption is associated with thyroid disorders such as hypothyroidism, goiter, and autoimmune thyroid disease (ATD) as well as increased iodine requirement in certain cases. However, the anti-thyroid component(s) in soy are yet to be identified and the molecular mechanism(s) involved remain unclear. This study examined the effects of soy isoflavones (ISF) on iodide uptake and expression of thyroglobulin (Tg) and sodium/iodide symporter (NIS) in thyrocytes. Fischer rat thyroid cells (FRTL) were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…(29) In vitro studies have demonstrated that isoflavones inhibit thyroid peroxidase (TPO) and inhibit iodide. (30) However, other studies using different preparations for up to 3 years have not shown changes in thyroid hormones. (31) In patients with subclinical hypothyroidism, the soy protein and isoflavone combination has been shown to increase the risk of developing overt hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…(29) In vitro studies have demonstrated that isoflavones inhibit thyroid peroxidase (TPO) and inhibit iodide. (30) However, other studies using different preparations for up to 3 years have not shown changes in thyroid hormones. (31) In patients with subclinical hypothyroidism, the soy protein and isoflavone combination has been shown to increase the risk of developing overt hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Much more recently, soya isoflavones were shown to inhibit thyroid peroxidase in vitro and in vivo in rats although rat thyroid function remained normal (26) . Others have reported that in rats while soya isoflavones inhibit synthesis of thyroglobulin and thyroid hormones, availability of thyroid hormone in peripheral tissues may increase (27) . The observation that people living in Asian countries have consumed soya foods for centuries with no perceptible thyrotoxic effects suggests their safety in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Por outro lado, a soja tem gerado preocupação sobre a função da glândula tireoide. 43 Pacientes com hipotireoidismo subclínico apresentam risco três vezes maior de desenvolver hipotireoidismo com suplementação de 16mg fitoestrógenos da soja ao dia. 44 Em estudo realizado com mulheres na menopausa, 45 75mg de isoflavonas reduziram os níveis de T3 livre, bem como aliviaram os sintomas da menopausa.…”
Section: Sojaunclassified